Facts and prevailing myths on COVID-19 among the general public, India: a cross-sectional survey - Meena, Keval Singh; Nambiar, Saugandhika P.; Kumari, Yogita; Joseph, Hepsi Bai; Shetty, Asha P. (International Journal Of Community Medicine And Public Health, 2021)
Background: COVID-19 is not a new disease for this world, but it shows alarming effects globally, and its sudden increase in incidence and spread is causing misperception and fear among the general population. The aim of this study was to assess the myths about COVID-19 among the general public, India. Methods: Cross-sectional survey was conducted using a convenient sampling technique to assess the myths on COVID-19 among 367 general public, India. The material used to collect the data was sociodemographic proforma and a structured questionnaire with 20 dichotomous questions with ‘Yes’ or ‘No’ option covering the transmission treatment and prevention myths on COVID-19. Data were collected through an online platform using Google forms and analyzed using R software. Results: The study identified six top myths on COVID-19. Taking a hot bath prevents coronavirus infection (93.5%), thermal scanners fail to detect COVID-19 (59.7%), prolonged use of face mask prevents COVID-19air entry (42.5%), houseflies transmit COVID-19 disease from one person to other (33.8%), mosquito bite transmits coronavirus (32.4%), and only older people and children are more susceptible to COVID-19 (30.8%). Conclusions: Myths were existed regarding COVID-19 due to lack of awareness. Awareness activities and strategies should be encouraged to reach all possible communication mean to erase the emerging myths. Besides, awareness should be enhanced by mass media or another portal in-order to follow the evidence-based preventive practices, including social distancing, cough and mask etiquette, hand hygiene, and other infection control measures to protect everyone from infection.